Transient Absorption Phenomena in Synthetic HPHT and CVD Diamonds for a Fast Timing in Nuclear Instrumentation - Buganov, O.; Tikhomirov, S.; Barbarchik, E.; Korjik, M.; Fedorov, A.; Mechinsky, V.; Tamulaitis, G. (Communications in Physics, 2017)
In this study, we investigate  transient phenomena in synthetic diamonds  obtained by High Pressure High Temperature and Chemical Vapor Deposition methods. Study was aimed at searching for inorganic crystalline media combining ionizing radiation detecting properties and non-linear absorption of ultra-short laser pulses. The nonlinear pump-and-probe optical absorption technique with of 140 fs laser pulses was used to study the effects.